PENGARUH PENGGUNAAN STRATEGI REALITA DALAM KONSELING KELOMPOK TERHADAP RASA RENDAH DIRI SISWA KELAS XII-IPA SMA Dr. SOETOMO SURABAYA - Iltizamah Iltizamah (HELPER, 2017)
Abstract: Low self esteem is a feeling which happens of the individual because of his judgment that himself is underestimating and also does not have valuable ability. The purpose of this research is to know the significance influence of the used of reality strategy in group counseling to students’ low self esteem at grade XII-Science of SMA Dr. Soetomo Surabaya. It is because the high of low self esteem is behavior which is not realistic and not responsible.The research design used Pre-Experimental research which the plan is One Group Pretest-Posttest. The population was from grade XII- Science students of SMA Dr. Soetomo Surabaya which amount 80 students, from these population was taken 6 students for research sample which used purposive sampling technique, the choosing of this sample chose based from the high of the low self esteem score result in filling low self esteem- measuring scale.The data collection method was using measuring scale which done the validity test and reliability test alpha cronbach..The results of the validity test measuring scale of low self esteem between 0.052-0.557, while the result of reliability test alpha cronbachs is 0.783. The research data was analyze using non parametrik statistic with the technique is Wilcoxon test in SPSS for Windows 16.0 version which got asymp.sig = 0,028. Because of the value asymp.sig = 0,001 < α = 0,028.From the result of this research was found that there is a positive influence which significance from the use of reality strategy in group counseling to low self esteem at grade XII-Science students of SMA Dr. Soetomo Surabaya. Keywords: Reality strategy, Group counseling, Students’ low self esteem.